Nhacʻ 50 praññʻʹ rvhe ra tu Tapʻ ma toʻ neʹ cacʻ khyī cacʻ reʺ teʺ sī khyaṅʻʺ myāʺ (Puṃ nhipʻ reʺ nhaṅʻʹ Cā ʼupʻ Thutʻ ve reʺ Lupʻ ṅanʻʺ, 1995)
Marching songs and war songs of the Burmese armed forces, with music; includes critical introductory notes; brought out on the 50th anniversary of the Burmese armed forces day.